Correlation between suboptimal vitamin D concentration and secondary hyperparathyroidism in women with low-energy fractures - Ćirković, Milan; Božić, Ksenija; Petronijević, Nataša; Nikolić, Tatjana (Vojnosanitetski pregled, 2021)
Background/Aim. Osteoporosis is the most common metabolic bone disorder worldwide characterized by decreased bone strength that predisposes to an increased fracture risk, especially in postmenopausal women. Today, over 25 million people, mainly women, suffer from this metabolic disorder. In addition to genetic predispositions, hormonal disorders, lifestyle, and insufficient vitamin D levels in the blood are significant risk factors for the occurrence of osteoporosis and low-energy fractures. The aim of our study was to analyze the incidence of osteoporosis and the correlation between vitamin D deficiency and secondary hyperparathyroidism in women of different ages with low-energy fractures. Methods. This cross-sectional study included 559 women who were not previously treated for osteoporosis. All women were clinically examined and their anamnesis of chronic illnesses, fractures, and therapies was taken. Height and weight were measured, and body mass index (BMI) was calculated. Risk factors for osteoporosis, including the concentration of 25-hydroxyvitamin D [25(OH)D] and parathyroid hormone (PTH), were measured. Vitamin D deficiency was defined as serum level of 25(OH)D less than 30 ng/mL (75 nmol/L). Results. The study included a total of 559 women, of which low-energy fractures were identified in 102 women. Women with fractures were older (63.69 ± 13.88 years) compared to women without fractures (54.39 ± 14.10 years) (p < 0.0005). Furthermore, BMI was also higher (27.75 kg/m2) in women with fractures compared to the other group (26.49 kg/m2) (p < 0.025). Out of 102 women with fractures, 88 were postmenopausal. The most frequent fractures were the humerus and radius fractures, 11.62% (65/559), followed by femoral neck fractures, 7.15% (40/559), and body vertebrae fractures, 3.04% (17/559). A significant decrease of the bone mineral density (BMD) in the spinal and the femoral neck sites was observed in women with femoral neck and body vertebrae fractures, but not in women with humerus and radius fractures. Vitamin D deficiency did not have a significant impact on fracture incidence. The increased concentration of PTH was statistically significant in women with femoral neck and body vertebrae fractures. Conclusion. In women with all three types of low-energy fractures, compared to women without fractures, significant risk factors for osteoporosis were age, BMD, and the strength of mechanical force during fall (estimated through BMI).
Keywords: osteoporosis; risk factors; vitamin d; fractures, bone; hyperparathyroidism, secondary; women